An investigation on parking facilities at the public and private hospital in Klang Valley / Hairul Amri Bin Shamsuddin - Shamsuddin, Hairul Amri (Faculty of Architecture, Planning and Surveying, 2015)
Hospital is one of the main infrastructures in this country that are vital in providing nursing care and medical supply for the person needed. There are two types of hospital that can be recognized, which are private hospital and public hospital. Public hospital is a hospital that is concerning the people or community and for all the people. Meanwhile, private hospital is a hospital that is owned by corporation or company that has specific purposes, including generating money. The overall finding of this dissertation there are many types of parking that are available in the country such as surface parking and multilevel parking. It has been found that lack of parking spaces provided by the hospital is one of the main reasons behind these parking spaces issues that become viral nowadays. The visitors have a hard time to find a space to park their vehicles in the hospital area and it consumes time. There are some suggestions to overcome this problem. One of them is to add more parking spaces for the visitors. It is compulsory in order to accommodate the number of visitors that come to the hospital. Overall the objective of this dissertation has been achieved by obtaining the data and analyzing all the factors that can contribute to it.